The Effectiveness of Clustering Technique on Students’ Writing Skill: A Study on Islamic Senior High School Students in Mandailing Natal, Indonesia - Heni Arwida; Eka Sustri Harida; Fitri Rayani Siregar (ELITE JOURNAL, 2023)
ABSTRACT This research is intended to investigate the Effectiveness of Clustering Technique on Students’ Writing Skill: a Study on Islamic Senior High School Students’ in Mandailing Natal, Indonesia. This research used quantitave research by using experimental method. The sample were X MIPA 1 as experimental group that consisted of 24 students and X MIPA 2 as control group that consisted of 24 students. The data were collected through pre-test and post-test in essay test form and analyzed by using Independent Sample T-test. The result of this research showed that the mean score of experimental group was higher than the mean score of control group. After doing t-test, the researcher found that tcount > ttable (6.98 > 2.012). It means Ha is accepted and H0 is rejected. It can be concluded that there was significant effect on students’ writing skill in learning by using clustering technique on Islamic Senior High School Students in Mandailing Natal, Indonesia. Keywords: Clustering Technique, Writing Descriptive Text